2008
DOI: 10.4314/ajpsy.v11i1.30255
|View full text |Cite
|
Sign up to set email alerts
|

Post traumatic stress disorder symptoms in a psychiatric population not presenting with trauma: a preliminary study

Abstract: A Af fr ri ic ca an n J Jo ou ur rn na al l o of f P Ps sy yc ch hi ia at tr ry y • February 2008 5 51 1 Introduction Post Traumatic Stress Disorder (PTSD) is an anxiety disorder currently defined by the coexistence of three clusters of symptoms, persisting for one month in survivors of a serious traumatic event .These clusters are:• Intrusive cluster -Intrusions can take the form of repeated, unwanted and uncontrollable thoughts of the trauma, and can include nightmare and/or flashbacks.• Avoidant cluster … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 4 publications
1
9
0
Order By: Relevance
“…To our knowledge, this is the first study using a semi-structured interview to have found such a low detection rate for PTSD in psychiatric outpatients. Two studies using self-report screening instruments yielded detection rates comparable to ours: Howgego et al7 found that a PTSD diagnosis was found in the medical records of only one in 27 PTSD-positive patients (3.7%), while Mkize8 reported that none of the 18 PTSD-positive patients were diagnosed in their medical records.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…To our knowledge, this is the first study using a semi-structured interview to have found such a low detection rate for PTSD in psychiatric outpatients. Two studies using self-report screening instruments yielded detection rates comparable to ours: Howgego et al7 found that a PTSD diagnosis was found in the medical records of only one in 27 PTSD-positive patients (3.7%), while Mkize8 reported that none of the 18 PTSD-positive patients were diagnosed in their medical records.…”
Section: Discussionsupporting
confidence: 74%
“…In addition to these studies, four others4,5,7,8 have examined current PTSD prevalence in psychiatric outpatients, although they used self-report screening instruments rather than a semi-structured diagnostic interview. In these studies, the prevalence ranged from 7% in Norway5 to 46% in Sweden 4.…”
Section: Discussionmentioning
confidence: 99%
“…This normalization dynamic has been shown to be useful in early traumatic stress alleviation, but it may not be enough to prevent the disorder (De Villiers, ). Consequently, people may not view their symptoms as serious enough to warrant professional attention (Carey et al., ; Mkize, ).…”
Section: Discussionmentioning
confidence: 99%
“…Other methods of assessment may include questionnaires such as the Traumatic Life Events Questionnaire (TLEQ) (Kubany et al, 2002), but these are not routinely used. Clinical practice, therefore, may potentially lead to the underdiagnosis of PTSD, and prevent appropriate management and assessment of outcomes (Mkize, 2008). Adequate screening for all forms of psychopathology, including PTSD, may be hindered by a high clinic workload, limitations placed on time for consultations, and working in a cross-cultural setting (Carey, Stein, ZunguDirwayi, & Seedat, 2003).…”
Section: Introductionmentioning
confidence: 99%